Factory Southern Africa? : SACU in Global Value Chains - Farole, Thomas (World Bank, Washington, DC, 2016)
Once concentrated among a few large economies, global flows of goods, services, and capital now reach an ever-larger number of countries worldwide. Global trade in goods and in services both increased 10 times between 1980 and 2011, while foreign direct investment (FDI) flows increased almost 30-fold. A value chain is global when some of these stages are carried out in more than one country, most notably when discrete tasks within a production process are fragmented and dispersed across a number of countries. Southern African Customs Union (SACU) - region global value chains (GVCs) are both a new reality and significant opportunity for expanding non-commodity exports to support growth, diversification, and job creation in the region. The task-based nature of GVCs creates opportunities for developing countries to establish very quickly a position in global trade within a sector in which they may have had no previous experience. For South Africa, GVCs are seen as a route to higher manufacturing exports and greater value addition. For other SACU countries, GVCs are seen as a route to diversification and global integration, and to leverage the possibility of greater investment from South Africa itself. The main objectives of the study are as follows: (i) to understand trends of GVC participation and competitiveness of South Africa and the wider SACU region, the outcomes from this participation (exports, jobs, and productivity), and the factors that determine competitiveness; (ii) to map the extent of value chain integration across the region and identify barriers to deeper integration; and (iii) to identify policies and actions that will be required to develop a globally competitive, high value-adding factory Southern Africa.